Revealing the dynamic changes of metabolites and molecular mechanisms of chlorogenic acid accumulation during the leaf development of Vaccinium dunalianum based on multi-omic analyses - Zhang, Anmian; Liu, Jiaxin; Li, Weicheng; Yang, Lihong; Duan, Wenjin; Zhao, Ping; Pu, Zhiyu; Ding, Yong (Frontiers in Plant Science, 2024)
Vaccinium dunalianum, a medicinal plant, is utilized for Quezui Tea production from its leaf buds and young leaves. Despite prior research on V. dunalianum revealing several medicinal compounds, the comprehensive variations in metabolites during its growth and development, along with the molecular mechanisms underlying high chlorogenic acid (CGA) yield, remain unclear. Through a joint analysis of transcriptomics and proteomics, our study first identified 15 key structural genes and 3 transcription factors influencing CGA biosynthesis in V. dunalianum, offering new evidence to understand its regulatory network. Furthermore, non-targeted metabolomics analysis provides the first extensive report on the metabolic profile of V. dunalianum, furnishing a valuable dataset for deeper exploration of its nutritional and medicinal value, and the development of a quality evaluation system for its product Quezui Tea. This study offers the most comprehensive molecular information on V. dunalianum, marking a significant step toward understanding and enhancing the plant's potential for medicinal and nutritional applications. Additionally, this study also reveals V. dunalianum holds promise as a natural antioxidant source for functional foods, providing data support for network pharmacology.